The Ethics of Quality: Problems and Preconditions - Nayebpour, Mohamad R. (Journal of business ethics, 2003)
A number of advocates for TQM contend that firms who embrace TQM will automatically and naturally act in ethically sound ways (Roth, 1993; Pace, 1999; Steeples, 1994). This claim is a strong one. This paper assesses its truth. We consider the many ways in which quality initiatives, if undertaken in good faith, can foster sound ethics. We explore the various ways in which TQM presupposes, and thus cannot engender, ethical behavior. And, finally, we identify some of the ethical blind spots in quality initiatives and TQM. We propose that if TQM is undertaken by thoughtful people who take steps to correct its ethical blind spots and who understand the need for an ethical underpinning, then TQM and ethics will prove mutually reinforcing.